The Influence of Environment, Social and Governance on Optimal Portfolio - Risal Rinofah; Pristin Prima Sari; Yhoga Heru Pratama; Irwan Trinugroho; Galuh Mira Saktiana (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance on optimal portfolio formation among energy and mineral companies listed on the Indonesia Stock Exchange (IDX). It further investigates the individual contribution of each ESG dimension in explaining portfolio optimization. Method: This study employs a quantitative research design using secondary data from the sustainability reports and annual reports of energy and mineral firms listed on the Indonesia Stock Exchange during 2020–2024. A purposive sampling technique was applied, resulting in 32 firms (160 firm-year observations). ESG performance was measured using the Global Reporting Initiative (GRI) indicators, while the optimal portfolio was assessed based on expected return and portfolio risk. The hypotheses were tested using multiple linear regression analysis. Findings: The findings reveal that Environmental, Social, and Governance (ESG) jointly have a significant effect on optimal portfolio performance. Partially, environmental and governance dimensions positively influence optimal portfolios, whereas the social dimension does not show a significant effect. The results indicate that investors place greater emphasis on environmental and governance practices than social initiatives when evaluating optimal portfolios in the Indonesian energy and mineral sector. Novelty: This study extends the ESG literature by integrating GRI-based ESG disclosure with optimal portfolio theory in the context of Indonesia's energy and mineral sector. Unlike previous studies that primarily examine the relationship between ESG and firm performance, this research provides empirical evidence on how individual ESG dimensions contribute to portfolio optimization using expected return and risk as the investment performance framework.